2023
DOI: 10.1002/jgf2.613
|View full text |Cite
|
Sign up to set email alerts
|

Footcare knowledge and practice among diabetic patients attending primary health care centers in Jazan region, Saudi Arabia

Abstract: Background Diabetic foot is one of the significant complications of diabetes mellitus, associated with a high risk of morbidity and mortality. Patients' knowledge of, and willingness to practice, good footcare are essential and may decrease these risks. This study was conducted to assess adult diabetic patients' knowledge of footcare and willingness to put their knowledge into practice. Method A cross‐sectional observational study was conducted on adult diabetic patients in the central area of the Jazan Region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…Enterobacteriaceae were shown to be the most common family of bacteria recovered from UTI patients in our study. This result is consistent with earlier studies conducted in several countries, including Saudi Arabia [13,14], where E. coli was found to be the most commonly isolated bacterium for UTIs, followed by K. pneumoniae. In our study, Gram-positive cocci, such as E. faecalis, accounted for nearly a third of UTI cases.…”
Section: Discussionsupporting
confidence: 93%
“…Enterobacteriaceae were shown to be the most common family of bacteria recovered from UTI patients in our study. This result is consistent with earlier studies conducted in several countries, including Saudi Arabia [13,14], where E. coli was found to be the most commonly isolated bacterium for UTIs, followed by K. pneumoniae. In our study, Gram-positive cocci, such as E. faecalis, accounted for nearly a third of UTI cases.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, a higher proportion of foot care practice was found among patients who did not experience a foot ulcer (88.9%), amputation (97.2%), and did not have ulcers, sores, or blisters on their feet (91.7%), did not have blood or discharge in their socks (99.1%), and had no callus (74.1%). Consistent with these findings, the results of previous similar studies reported that diabetic patients without diabetes complications had significantly higher knowledge and better foot care practice than those with complications [29,44,45]. These findings were consistent with the results by Guell et al [46], who reported that lower knowledge and practice scores, as expected, might make patients more vulnerable to complications.…”
Section: Discussionsupporting
confidence: 90%
“…These results align with previous international studies reporting deficiencies in knowledge and practice regarding foot care among patients with diabetes [26][27][28]. A recent similar study conducted in Saudi Arabia on more than 400 adult patients with diabetes in Jazan showed that 56% of the patients had wrong answers to foot care knowledge questions [29].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation